PINOCEMBRIN ATTENUATES COLISTIN-INDUCED HUMAN RENAL PROXIMAL TUBULAR CELL APOPTOSIS - Worakajit, Nichakorn; Chabang, Napason; Soodvilai, Sirima; Tuchinda, Patoomratana; Soodvilai, Sunhapas (Thai Bulletin of Pharmaceutical Sciences, 2021)
Colistin is an essential last-resort polypeptide antibiotic widely used for treatment of multidrug-resistant (MDR) caused by the emergence of gram-negative bacterial infection. However, the adverse effect of colistin has been associated with nephrotoxicity. The nephrotoxicity is mediated by excessive production of reactive oxygen species (ROS) and mitochondria damage in renal cells. Pinocembrin, one of the dominant bioactive compounds extracted from Boesenbergia rotunda, presents antioxidative properties and preventive role against mitochondrial dysfunction. Thus, this study aimed to investigate the renoprotective effects and cellular mechanisms of pinocembrin against colistin-induced renal proximal tubular cells toxicity. The results revealed that colistin treatment significantly reduced cell viability and enhanced apoptosis of human renal proximal tubular cells, RPTEC/TERT1 cells, compared with vehicle. These effects were attenuated when co-treated with pinocembrin. Moreover, colistin-activated cytotoxicity including ROS generation, loss of membrane potential and upregulation of apoptotic proteins expression such as cytochrome C and caspase-3 were suppressed in pinocembrin treatment. Therefore, pinocembrin exerts protective effects against human renal proximal tubular cells apoptosis by ameliorated colistin-induced mitochondrial impairment.